Description Of The Characteristics, Knowledge And Support Of Husbands In Acceptors Of Long-Acting Reversible Contraception Methods (LARC) - Djani, Gaudensia Cindy Claresta; Sriasih, Ni Gusti Kompiang; Rahyani, Ni Komang Yuni (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
Contraceptive services play an important role in preventing pregnancy and reducing maternal mortality. One of the effective strategies in family planning programs is the use of Long-Acting Reversible Contraception (LARC), such as intrauterine devices (IUDs), implants, and sterilization, which offer high effectiveness and long-term protection. This study aimed to describe the characteristics, knowledge, and husband support among family planning acceptors using long-acting reversible contraception in the working area of Public Health Center III, South Denpasar District Health Office. This study employed a quantitative descriptive design with a cross-sectional approach. The researchers analyzed the characteristics, knowledge, and husband support among LARC acceptors in the study area. The results showed that most respondents were aged 25–35 years (76%), had completed senior high school or vocational high school education (70%), and worked as private employees (50%). More than half of the respondents had a high income (52%). The majority demonstrated good knowledge of LARC (64%). The most common types of husband support were informational and instrumental support (98%). In conclusion, most respondents were of productive age, had relatively high educational backgrounds, worked as private employees, and had high income levels. Although respondents generally had good knowledge and husband support, further improvement is still needed to optimize the implementation of LARC programs.